2013
DOI: 10.1186/1475-2875-12-382
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of clinically captured and confirmed malaria among HIV seropositve clinic attendants in five hospitals in Ghana

Abstract: BackgroundMalaria is associated with an increase in HIV viral load and a fall in CD4-cell count. Conversely, HIV infection disrupts the acquired immune responses to malaria and the efficacy of antimalarial drugs. This study was carried out in five Ghanaian hospitals to estimate the prevalence of clinically confirmed malaria among HIV patients by evaluating their hospital records.MethodsThis retrospective descriptive cross sectional study reviewed and collected data on malaria, using Case Record Forms from HIV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
5
1
Order By: Relevance
“…Our results seem to be very low compared to the Tay and Fo studies where prevalence were respectively 11.75% and 11.8% [19] [20]. However compared to Adu-Gyasi in Ghana (4.4%) our prevalence is high [21]. Difference in timing of study would explained difference in results obtained in Tay and Fo due to the fact that these studies were conducted in the period of the year where malaria endemicity is high [22].…”
Section: Discussioncontrasting
confidence: 76%
“…Our results seem to be very low compared to the Tay and Fo studies where prevalence were respectively 11.75% and 11.8% [19] [20]. However compared to Adu-Gyasi in Ghana (4.4%) our prevalence is high [21]. Difference in timing of study would explained difference in results obtained in Tay and Fo due to the fact that these studies were conducted in the period of the year where malaria endemicity is high [22].…”
Section: Discussioncontrasting
confidence: 76%
“…In a study in other parts of Ghana by Adu-Gyasi et al [ 25 ], malaria prevalence in HIV positive patients was lower than the average national malaria prevalence. This is similar to the present study results; and may be attributed to co-trimoxazole (CTX) prophylaxis (given with anti-retroviral therapy as recommended by the Ghana National Aids Control Programme) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study realized in Malawi on the attributable-fraction of malaria in febrile episodes, showed that 15% of reported fevers in HIV-positive subjects were due to Plasmodium infection [50]. Another study carried out in Ghana revealed that, the prevalence of confirmed malaria by the laboratory was 4.4% in seropositive patients [8]. The above mentioned estimates found in seropositive patients of endemic areas were both higher than the value obtained here in Western highland of Cameroon, which was 0.15%.…”
Section: Malaria-attributable Fraction Of Fever Episodesmentioning
confidence: 99%
“…In holoendemic areas of malaria, plasmodial infection could have effects on HIV acquisition, as well as its progression and response to therapy [5][6][7]. Moreover, HIV infected individuals when bearing malaria parasites, have significant increase in viral load and decrease in T-lymphocytes CD4 count [8]. The phenomenon is even more severe in HIV infected adults [9].…”
mentioning
confidence: 99%